CHEMICAL AGENTS AND SHADING LEVELS FOR THE PRODUCTION OF PEPPER SEEDLINGS - Binotti, Eliana D. C.; Costa, Edilson; Binotti, Flavio F. da S.; Batista, Thiago B. [UNESP] (Soc Brasil Engenharia Agricola, 2018)
The aim of this study was to evaluate protected cultivation environments with different levels of shading and application of foliar chemical agents, on growth, photosynthetic pigments and seedling quality of Capsicum frutensens L. The experiment was developed at the State University of Mato Grosso do Sul, University Unit of Cassilandia, with chili pepper. Three cultivation environments (screen of 18, 35 and 50% of shading) and six leaf chemical agents were used [(1) control - without application; (2) Nitrogen (N) 1%; (3) Paclobutrazol 50 mg L-1 + N 1%; (4) Auxin 0.05 g L-1 + N 1%; (5) Gibberellin 0.05 g L-1 + N 1%; and (6) Auxin 0.05 g L-1 + Gibberellin 0.05 g L-1 + N 1%]. Each environment was considered an experiment in which the completely randomized design was adopted and, afterwards, a joint analysis of the same was carried out. The growth and the biometric relations were evaluated. The leaf nitrogen application positively influences the growth and chlorophyll content of pepper seedlings; the application of nitrogen + growth regulator via foliar produces seedlings with higher growth and biometric relations in environments with 50% shading. For the production of seedlings with desirable morphological and physiological aspects, it is recommended to use a foliar application of paclobutrazol + nitrogen in an environment with 50% shading.
Keywords: auxin; Capsicum frutensens L; gibberellin; light; nitrogen; paclobutrazol